Elie Wiesel : Jewish, Literary, and Moral Perspectives - Rosen, Alan, 1954-; Katz, Steven T., 1944- (Jewish literature and culture., 2013)
With this analysis Wiesel surely attempts to enter the historical context of persecution that defined Rabbi Shimon's life and milieu. But he also reclaims for his own persecuted generation of Holocaust survivors the talmudic sage's experience of oppression and the wisdom that steered a path through it. In Wiesel's universe of historical study, the Jewish past gives direction to the Jewish present (and future), while the Jewish present-particularly the lengthy shadows cast by the Holocaust-orients our approach to the past, dictates the questions we ask of it, and shows our profound relationship to those who inhabited it.